Impact of atrial fibrillation on inflammatory bowel disease hospitalizations—a nationwide retrospective study. Issue 6 (2nd November 2021) - Kichloo, Asim; Dahiya, Dushyant Singh; Shaka, Hafeez; Jamal, Shakeel; Khan, Muhammad Zia; Wani, Farah; Mehboob, Asad; Kanjwal, Khalil
Abstract: Systemic inflammation seen in inflammatory bowel disease (IBD) may cause electrophysiological changes in the atria leading to atrial fibrillation (AF). We analyzed data from the National Inpatient Sample for 2018 to identify all adult hospitalizations with a primary diagnosis of IBD, which were further divided based on the presence or absence of AF. The primary outcome was inpatient mortality while the secondary outcomes included inpatient complications, mean length of stay, and mean total hospital charge. We identified 92, 055 IBD hospitalizations, of which 3900 (4.2%) had AF and 88, 155 (95.8%) served as controls. IBD hospitalizations with AF were older (70.9 vs. 45.0 years, P < 0.001) and had a higher association with comorbidities compared to the non-AF cohort. Furthermore, the AF cohort had significantly higher adjusted odds of inpatient mortality (2.05% vs. 0.24%; adjusted odds ratio 2.07; 95% confidence interval [CI] 1.09–3.90; P = 0.025), longer length of stay (6.5 vs. 4.9 days; incidence rate ratio 1.23; 95% CI 1.14–1.33; P < 0.001), and higher total hospital charge ($14, 587 vs. $11, 475; incidence rate ratio 1.26; 95% CI 1.15–1.38; P < 0.001). Additionally, complications such as acute respiratory failure, pulmonary embolism, and necessity of blood product transfusion were more common for IBD hospitalizations with AF than those without.